A Complementary Health Approach to Tuberculosis Care: Antimycobacterial Activity of Red Betel Leaf and Shallot Ethanol Extracts - Bangun, Seri Rayani; Sinaga, Desriati; S, R. Oktaviance.; Novitarum, Lilis; Karo, Mestiana Br; EL- Matury, Herlina J. (Chakra Brahmanda Lentera Institute, 2026)
Background: Tuberculosis (TB) remains a major global health problem, particularly in low- and middle-income countries. The emergence of drug-resistant Mycobacterium tuberculosis has increased interest in alternative antimicrobial agents from medicinal plants. Red betel leaf (Piper crocatum) and shallot (Allium cepa L.) contain bioactive compounds with potential antibacterial activity. This study aimed to evaluate the inhibitory effect of ethanol extracts of red betel leaf and shallot at different concentrations on the growth of Mycobacterium tuberculosis in vitro. Methods: A pre-experimental one-group study was conducted in the Microbiology Laboratory of Santa Elisabeth School of Health Sciences, Medan. Mycobacterium tuberculosis isolates from sputum samples were cultured and tested using the disk diffusion method. Ethanol extracts of red betel leaf and shallot were prepared and tested at concentrations of 40%, 60%, 80%, and 100%. Phytochemical screening was performed, and inhibition zones were measured for three days. Data were analyzed using one-way ANOVA followed by Tukey’s HSD post hoc test. Results: Phytochemical analysis identified alkaloids, flavonoids, tannins, and saponins in the extracts. The mean inhibition zone diameters increased with extract concentration, ranging from 2.67 ± 0.58 mm at 40% to 11.67 ± 0.58 mm at 100%. One-way ANOVA showed a statistically significant difference among concentrations (F(3, 8) = 134.25, p < .001), and all pairwise comparisons were significant. Conclusion: Ethanol extracts of red betel leaf and shallot demonstrated significant, concentration-dependent inhibitory activity against Mycobacterium tuberculosis in vitro, supporting their potential as complementary antimicrobial agents and warranting further research in nursing and health sciences.